Overview of CBTS Pillar 1 Program Evaluation Stop Open Defecation (SOD) at the Public Health Center, Taman Sari District, West Jakarta City in 2022 - Sekar Wijayanti, Febriana; Handayani, Putri; Azteria, Veza; Nitami, Mayumi (Rifa'Institute, 2023)
Introduction: Sanitation is one of the problems faced by Indonesia. One of the government's efforts to overcome it is through the National Community-Based Total Sanitation (CBTS) program. Taman Sari District has the lowest achievement of Proper Sanitation in West Jakarta City, which is equal to 83.7%, out of 35,147 households there are still 5698 households who practice open defecation or 16.2%. Objective: This study aims to find out the Evaluation Overview of the CBTS Pillar 1 program Stop Open Defecation (SOD) at the Tamansari District Health Center in 2022. Method: This type of research is descriptive analytic with qualitative methods, with a total sample of 6 people, consisting of the Head of the Public Health Center, three Sanitarians, 1 village chief, 1 Sanitarian from the West Jakarta Health Office. Result and Discussion: Based on the research results, it was found that the planning process was good in terms of process and budget availability, but still needed improvement in the quality of officers and policy implementation. Conclusion: In the implementation process it is necessary to have new strategic interventions both during socialization, triggering, verification and declaration by involving cross-sectors and related programs, then for the monitoring and control process it is recommended to carry out evaluations related to changes in community behavior, especially open defecation.